A time-frequency analysis of the housing construction time as the basis for making decisions on the construction market (the case study of Poland) - Mach, Łukasz; Zmarzły, Dariusz; Dąbrowski, Ireneusz; Frącz, Paweł (Analiza czasowo-częstotliwościowa czasu budowy nieruchomości mieszkaniowych jako podstawa podejmowania decyzji na rynku budowlanym (studium przypadku Polski), 2020)
Due to the increasingly complex market situation characterized by the growing variability of its determinants, making accurate decisions is riddled with an increasing risk of error. Widely used economic methods for analyzing market phenomena with a trajectory of time series has proved insufficient in many cases. Hence, it becomes necessary to seek more precise analytic methods, based on which it is be possible to obtain more precise mapping and relations in real-life activities. The goal of the present study is to apply the time-frequency analysis in the domain of real estate. Based on the application of, among others, Savitzky-Golay filtering, spectral density analysis, or cross-correlation, the time-frequency analysis will render it possible to precisely identify the parameters that selectively determine the housing market. The obtained results will make it possible to decrease the informational gap in the investment decision-making process in the housing market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 54-71